Model Supervisi yang Efektif untuk Meningkatkan Kinerja Pengajaran di Sekolah: Systematic Literature Review - Nur Rahma (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to analyze the role of principal supervision in improving teacher performance and learning quality, and to identify the most effective supervision approaches based on a review of the current literature. This study used the Systematic Literature Review (SLR) method by analyzing 15 scientific articles indexed in Google Scholar published between 2021 and 2024. The selection process was carried out based on inclusion and exclusion criteria, then the data was analyzed thematically to identify patterns and key findings. The results showed that a collaborative and constructive feedback-based supervision approach significantly improved teachers' pedagogical and professional competence. Collaborative supervision encouraged teachers' active participation in self-development, while constructive feedback helped improve teaching practices continuously. This study provides an up-to-date synthesis of principal supervision models with a focus on collaborative approaches and constructive feedback, which have not been comprehensively discussed in the context of teacher performance improvement. These findings recommend the need to strengthen school policies that support the implementation of collaborative and feedback-based supervision. In addition, specific training for principals in implementing academic supervision needs to be optimized to ensure the effectiveness of the supervision process. This research contributes to the development of a more effective and sustainable academic supervision model, and serves as a reference for policy makers, school principals, and educational researchers in efforts to improve the quality of learning in schools.